Inflation Developments in the Euro Area Since the Onset of the Pandemic - Christiane Nickel; Gerrit Koester; Eliza Lis (Intereconomics)
Abstract There is hope that the Russian war on Ukraine could expedite the energy transition in Europe leading to a new and more environmentally sustainable steady state.